2020
DOI: 10.3389/fmars.2020.610886
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and Multi-Gene Phylogeny of the Subfamily Nothoholostichinae (Ciliophora, Hypotrichia), With Integrative Description of a New Marine Species Nothoholosticha luporinii n. sp.

Abstract: Morphogenesis of ciliated protists attracts a lot of attention, because their huge morphological diversity is related to formation of ciliary structures during cell division. In the present work, the morphology and morphogenesis as well as the phylogenetic position of a new, marine hypotrich ciliate, Nothoholosticha luporinii n. sp., were investigated. The new species is characterized by having a combination of the following features: a bicorona whose anterior row contains four frontal cirri and posterior row … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Monophyly of trachelostylids was corroborated not only by morphological data but also by multigene phylogenetic analyses ( Figure 9 ), albeit not by single-gene analyses ( Figure 8 ). Various studies have already shown that concatenation of 18S, ITS1-5.8S-ITS2, and 28S rDNA sequences might lead to better resolved phylogenetic trees in the subclass Hypotrichia than 18S rDNA sequences per se (e.g., Huang et al, 2016 ; Obert and Vd’ačný, 2020 ; Zhang et al, 2020b ; Wang et al, 2021b ). The same applies also to the monophyletic origin of the genus Trachelostyla , which was only indicated in 18S rDNA phylogenies ( Figure 8 ) although well recognizable in the multigene trees ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monophyly of trachelostylids was corroborated not only by morphological data but also by multigene phylogenetic analyses ( Figure 9 ), albeit not by single-gene analyses ( Figure 8 ). Various studies have already shown that concatenation of 18S, ITS1-5.8S-ITS2, and 28S rDNA sequences might lead to better resolved phylogenetic trees in the subclass Hypotrichia than 18S rDNA sequences per se (e.g., Huang et al, 2016 ; Obert and Vd’ačný, 2020 ; Zhang et al, 2020b ; Wang et al, 2021b ). The same applies also to the monophyletic origin of the genus Trachelostyla , which was only indicated in 18S rDNA phylogenies ( Figure 8 ) although well recognizable in the multigene trees ( Figure 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…nov. and T. pediculiformis pop. 1 were investigated using a combination of detailed in vivo observation and protargol impregnation as described by Zhang et al (2020b) . Morphometric data were obtained from living and protargol-impregnated specimens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, investigations based on multigene trees have been increasingly used for phylogenetic studies and generally produce more robust results than those based on single gene markers (Gao et al, 2013 , 2016 , 2017 ; Sun et al, 2020 ; Wang, Wang, et al, 2017 ; Zhang et al, 2020 ). Multigene analyses usually include nSSU‐rRNA, ITS1‐5.8S‐ITS2 and nLSU‐rRNA genes, which are in the same chromosome (Wang, Wang, et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Urostylids, with more than 200 described species, are one of the largest groups in the subclass Hypotrichia (Berger, 2006). Studies from the past few decades have revealed that this group is even more diverse than previously thought, and many new species are likely awaiting discovery (Berger, 2006;Jiang et al, 2013;Jo et al, 2015;Kim et al, 2016;Song and Shao, 2017;Chen et al, 2018Chen et al, , 2020Zhu et al, 2019;Shao et al, 2020;Xu et al, 2020;Zhang et al, 2020a). In addition, some classifications at the family and genus levels within this group (e.g., Bakuellidae Jankowski, 1979 andAnteholosticha Berger, 2003), and their systematic relationships, remain confusing (for reviews, see Berger, 2006;Huang et al, 2014;Lyu et al, 2015Lyu et al, , 2018Moon et al, 2020;Zhang et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%